C48 PROGNOSTIC IMPACT OF ECHOCARDIOGRAPHIC RESTRICTIVE FILLING PATTERN IN PATIENTS AFFECTED BY HYPERTROPHIC CARDIOMYOPATHY AND PRESERVED SYSTOLIC EJECTION FRACTION. (18th May 2022) - Priotto, F; Albani, S; Mabritto, B; Luceri, S; Pizzuti, A; Bongioanni, S; Tomasello, A; Buongiorno, A; Parrini, I; De Rosa, C; Ricotti, A; Scacciatella, P; et al.
Abstract: Background: "Restrictive phenotype" is an uncommon presentation of Hypertrophic Cardiomyopathy (HCM), associated with severe functional limitation and poor prognosis. For this reason, current therapeutic aims are prevention of complications through periodic follow–ups and diagnostic investigations, up to the ICD placement. Objectives: The primary aim of this study was to evaluate the impact of the restrictive filling pattern in HCM on the incidence of complex composite outcome included arrhythmic events, events related to heart failure and general events, correlating it to clinical and imaging data. Methods: This study is an experimental, multicentric, retrospective and non–randomized analysis, including all patients over the age of 18 suffering from classical HCM, excluding phenocopies and systolic dysfunction. Patients were followed up and selected by specialized Centers of Trieste and Turin and divided by degree of diastolic dysfunction, particularly on the basis of the presence or absence of the restrictive filling pattern. Results: A total of 367 patients with HCM were included. Restrictive filling pattern was present in 23 patients (6.3%). This subgroup of patients was younger than all other patients (P < 0.001); percentage of ICD patients suffering from severe diastolic dysfunction at follow–up is significantly higher than patients without restrictive filling pattern (39.1% vs 4.1%, P < 0.001). On average, left atrial volume has larger sizes in restrictive filling pattern (109.7ml, SD 43.06 vs 82.8ml, SD 35.81, P = 0.003). Patients with restrictive filling pattern, compared to other patients, are more subjected to heart transplantation (8.7% vs 0.3%, P = 0.009) and hospitalized for heart failure (21.7% vs 7.8%, P = 0.028). Restrictive pattern was not an independent predictor of adverse events at the multivariable analysis. In our cohort, the independent predictors were found to be the left atrium diameter and the presence of LGE on CMR. Conclusions: In patients with HCM and preserved EF, the evidence of a restrictive diastolic pattern identifies a poor prognosis subgroup. Severe diastolic alteration was not associated with a significant independent role either for events related to heart failure, or for arrhythmic events during a median follow up of 7 years. However, the high rate of ICD implantation in patients with severe diastolic dysfunction suggests a high clinical perception of adverse events in this subgroup.